Nashoihul 'Ibad Karya Syekh Nawawi Al-Bantani Dan Pendidikan Kekinian - Lili Hidayati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: This paper is adressed to all the components involved in education. Teachers, parents, and students all become object of study in this paper. Featuring educational thinking Sheikh al-Nawawi al-Bantani in the book Nashoilul 'Ibad will add to the discourse of existing educational concepts. By displaying various Qur'anic verses, hadiths and saying of the scholars, Sheikh Nawawi explain that the educational process should involved all parties with all his energy, ability, and willingness. Totallty is peppered with religious fervor is what ultimately produces educational thought kaffah rivaling the concept of modern education that lack of religious values. Keywords: nashoihul 'ibad, Nawawi bantani, education, contempory.